Bordering seafarers at sea and onshore - Wemyss, Georgie (Frontiers in Sociology, 2023)
This paper uses a historically informed lens of coloniality, bordering and intersectionality to analyse maritime bordering discourses and practices that target seafarers recruited from the Global South who embody the border in their everyday lives. In seeking to explain the current context exemplified by the sacking of P&O Ferry workers and the recruitment of ‘foreign agency’ crews in March 2022, the paper foregrounds nineteenth and twentieth century maritime bordering legislation on ships and onshore focusing on public/private bordering partnerships between governments, shipping companies and unions. Illustrative examples, including from the ‘Lascar Accommodation in the UK’ India Office archives of the 1920s are drawn on to consider the implications of these earlier bordering discourses and practices for twenty-first century British citizenship and belonging. Attending to imperial bordering regulations that created the racialized and class-defined labour category of ‘lascars’, explains the ‘common sense’ designations of seafarers recruited in the Global South and their families as potential ‘illegal migrants’ and in doing so it constitutes the long history of the public/private partnerships that constitute the UK’s ‘hostile environment’ immigration policies.